l-Menthol sprayed on gastric mucosa causes edematous change - Mori, Akihiro; Hachiya, Hiroki; Yumura, Takayuki; Ito, Shun; Hayashi, Shintaro; Nozaki, Masashi; Yoshida, Atsui; Ohashi, Noritsugu (Endoscopy International Open, 2014)
Background and study aims:l-Menthol (LM), sprayed on the distal gastric mucosa, is a safe antispasmodic agent used during esophagogastroduodenoscopy (EGD). However, it seems to affect gastric mucosal endoscopic findings. Therefore, we evaluated whether LM causes specific changes and impacts the endoscopic morphology of gastric lesions.Patients and methods: A total of 98 patients scheduled to undergo EGD were randomly assigned to receive LM solution (160 mg of 0.8 % LM added to 2.5 mL of indigo carmine [IC]; n = 49; LM group) or decuple-diluted IC solution without LM (n = 49; placebo group). We compared the incidence of specific mucosal changes and the difference in the endoscopic findings of several gastric lesions between these groups.Results: Annular-reticular – like mucosal changes appeared immediately after the administration of LM solution. This change was observed in 71.4 % of the LM group compared with 12.2 % of the placebo group (P < 0.01). In the placebo group, this change was observed in 14.7 % of subjects with atrophic gastritis compared with 6.7 % of those without atrophic gastritis (P = 0.39), whereas in the LM group, this change was observed in 84.8 % of subjects with atrophic gastritis compared with 43.8 % of those without atrophic gastritis (P < 0.01). Most early gastric cancers, erosions, and ulcers observed in this study became well demarcated after LM administration, although the incidence of gastric lesions did not differ significantly between the two groups.Conclusion: LM changes the gastric mucosa into edematous mucosa, and this occurs more frequently in atrophic gastric mucosa than in pathologic lesions. LM may facilitate the demarcation of pathologic gastric lesions without intestinal metaplasia.